Improving Projection of the Nasal Tip in Primary Endonasal Rhinoplasty - Pastorek, Norman; Cleveland, Patrick (Facial Plastic Surgery, 2021)
Gaining, improving, and maintaining nasal tip projection is one of the most essential elements of successful endonasal rhinoplasty. For years the hallmark of inadequate nasal tip projection following rhinoplasty has been the Polly beak deformity. Early rhinoplasty technique consisted of intracartilaginous excision of the cephalic margin of the lower lateral cartilages, cartilage and bony hump reduction, and osteotomies. Some of these simple rhinoplasties still look good decades later, however, many are conspicuous in their lack of nasal tip projection. The reason for this inconsistency in rhinoplasty results was the surgeon's inattention to the structural integrity and anatomical position of the LLC. The senior author uses a combination of suture, strut, and cartilage grafting techniques to achieve ideal projection in a manor tailored to each patient's unique anatomic needs.
Keywords: rhinoplasty; endonasal; nasal projection; nasal tip